MEMAHAMI NEGOSIASI IDENTITAS KEAGAMAAN PEREMPUAN MUSLIM DALAM PERNIKAHAN BEDA AGAMA DENGAN LAKI-LAKI KATOLIK - Andrei Seven Manuel Sirait; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Interfaith marriage presents complex communication dynamics, particularly regardinghow individuals maintain and negotiate their religious identities within marital life. This studyaims to understand the experiences of Muslim women in negotiating their religious identitiesin marriages with Catholic men. This research employs a phenomenological approachinvolving seven Muslim women who are married to Catholic spouses. Data were collectedthrough in-depth interviews and analyzed using phenomenological analysis to uncover themeaning of participants’ lived experiences. The findings reveal that religious identitynegotiation does not occur through open conflict but through everyday practices that arepersonal, contextual, and relational. Negotiation is carried out by positioning religioussymbols as personal needs within the domestic space, meaning that such symbols are notnecessarily displayed as public identity markers but are adjusted based on relational comfortwithin the family. In addition, religious practices are treated as private domains that areperformed in parallel without mutual interference, allowing differences in belief to coexistwithout escalating into conflict. In terms of food consumption, negotiation takes place throughthe management of halal and non-halal boundaries using practical adaptation strategies, suchas separating food or adjusting shared eating practices. Meanwhile, religious celebrations areredefined as social and familial moments rather than ritual participation, enabling involvementwithout compromising individual religious identities. Regarding children’s religiousupbringing, negotiation occurs through discussion and mutual agreement between partners,taking into account family values as well as the child’s individual autonomy. These findingsindicate that religious identity negotiation in interfaith marriage operates through theformation of personal boundaries, everyday adaptive strategies, and relational adjustmentsthat allow differing beliefs to coexist within the household.